Factors Associated with Problematic Alcohol Consumption among Adults in Putalibazar Municipality of Syangja District, Nepal - Rajeev Nepal; Jyoti Priyanka; Pradip Chhetri; Suruchi Godar; Pratigya Timsina; Saroj Doranga (Advances in Public Health)
Background. According to the WHO STEPS survey 2013 in Nepal, 17% of the surveyed population had consumed alcohol within the last 30 days. Alcohol consumption in Nepal is socially and culturally accepted in many ethnic groups. The purpose of this study was to determine various factors associated with problematic alcohol consumption among adults in Putalibazar Municipality of Syangja district. Methods. A community-based cross-sectional study was conducted between September 2020 and January 2021 among 300 adults between ages of 18–64 years in Putalibazar Municipality of Syangja district of Nepal. Using a pretested semistructure questionnaire, a face-to-face interview was performed for collecting the data. An Alcohol Use Disorder Identification Test (AUDIT) developed by the World Health Organization (WHO) was used as a guiding tool to determine the audit-risk level category among adults according to their drinking status. Respondents with scores 0–7 in AUDIT scores were considered as nonproblematic drinkers, while respondents scoring 8–40 in the AUDIT scores were considered as problematic drinkers. Bivariate and multivariable analysis was performed to find out the association between dependent and independent variables. Variables which were found statistically significant at 95% CI (p ≤ 0.05) during bivariate analysis were further analyzed using the logistic regression model in multivariable analysis to identify determinants associated with problematic alcohol consumption among adults. Results. The mean age of participants was 36.72 years with a ±10.81 standard deviation. A total of 56.3% of adults were problematic drinkers. The multivariable regression analysis model identified adults within the age group of 25–34 years and 35–44 years along with males significantly associated with problematic alcohol consumption. Adults within the age group of 25–34 years and 35–44 years were 7.4 times (AOR = 7.4, CI: 1.97–27.60) and 5.7 times (AOR = 5.7, CI: 1.58–20.56) more likely to be problematic drinkers than their counterparts who were from the age group of 55–64 years. Males were 6.9 times more likely to be (AOR = 6.9, CI: 3.35–14.26) problematic drinkers than females. Conclusion. Problematic alcohol consumption among males was common and significantly associated within the age group of 25–34 years and 35–44 years. This study concerns the need for policy makers to launch awareness programs and community-based interventional programs considering identified factors associated with excessive drinking.